Insulating high-thermal-conductivity gel and preparation method thereof

Through the synergistic action of modified copper powder, boron nitride and nanometal droplets, an efficient thermal conduction network and thermal conductivity path are formed, which solves the problems of insufficient thermal conductivity and electrical insulation performance of thermal gels, and achieves the combination of high thermal conductivity and insulation. Suitable for the heat dissipation needs of precision electronic devices.

CN119119741APending Publication Date: 2024-12-13GUANGCHANG LIHUA TECH CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411221027.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-02
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The thermal conductivity of existing thermal gels is insufficient, and high thermal conductivity is mainly achieved by adding conductive fillers, resulting in insufficient electrical insulation performance and it is difficult to meet the heat dissipation needs of precision electronic devices.

Method used

Modified copper powder, modified boron nitride and nanometal droplets are used as solid-liquid mixed fillers, and modified by silane coupling agent to form an efficient thermal conduction network and thermal conduction path, while blocking electron migration, and preparing insulated high thermal conductivity glue.

Benefits of technology

An insulated high thermal conductivity gel with a thermal conductivity greater than 6.5W/(m·K) and a volume resistivity greater than 109Ω·cm is achieved, which improves the thermal conductivity and electrical insulation of the composite material, and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119741A_ABST
    Figure CN119119741A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of thermal management materials, and particularly relates to insulating high-thermal-conductivity gel and a preparation method thereof. The preparation method comprises the following steps: firstly, preparing modified copper powder, modified boron nitride and nano metal liquid drops respectively, forming a solid-liquid mixed filler by using a solid modified filler with a high heat conductivity coefficient and a liquid metal, and then adding the solid-liquid mixed filler into organic silicon gel. By utilizing the synergistic effect of the three fillers, the high heat conductivity and insulativity of the heat-conducting gel are realized, the heat conductivity coefficient of the prepared gel material is greater than 6.5 W / (m.K), and the volume resistivity is greater than 109 omega.cm; the preparation method of the insulating high-thermal-conductivity gel is simple and low in equipment requirement, and the prepared gel material is excellent in performance and suitable for industrial continuous and mass production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of thermal management materials, and in particular relates to an insulating high thermal conductivity gel and a preparation method thereof. Background Art

[0002] As electronic devices evolve towards miniaturization and high performance, the heat flux density of electronic components continues to increase, which poses unprecedented challenges to heat dissipation technology. Traditional heat dissipation materials, such as thermal grease and thermal pads, often seem to be unable to cope with high heat flux density and complex equipment structures. Thermal conductive gel, with its unique physical and chemical properties, such as high thermal conductivity, good flexibility and adaptability, has become an ideal material to solve this problem. It can not only fill the tiny gap between electronic components and radiators and improve heat conduction efficiency, but also adapt to various complex shapes of electronic devices and provide customized heat dissipation solutions. In addition, the environmental protection characteristics and reliability of thermal conductive gel are also important reasons for its attention. At a time when environmental protection regulations are becoming increasingly stringent, the non-toxic and non-corrosive silicon-based materials used in thermal conductive gel are easy to recycle and meet modern environmental protection requirements. At the same time, its stable chemical properties and good electrical insulation properties ensure the long-term stable operation of electronic equipment. Although some research progress has been made in thermal conductive gels, their thermal conductivity is still not high enough. The thermal conductivity of most thermal conductive gels is less than 5W / (m·K), and high thermal conductivity is mainly achieved by adding conductive fillers. They are conductive themselves, so it is difficult to meet the heat dissipation needs of increasingly sophisticated electronic devices.

[0003] At present, there are two major performance contradictions in the research and application of thermal management materials. First, although some materials have high thermal conductivity and can transfer heat quickly and efficiently, their electrical insulation performance is insufficient, which poses a safety hazard in high-power density and high-frequency electronic devices. For example, some metal-based composites and some high-thermal-conductivity polymer-based composites, although they have high thermal conductivity, are limited in their use in application scenarios with strict insulation requirements due to the conductive properties of metal fillers or the charge transfer at the interface between fillers and the matrix. Secondly, although other materials have excellent electrical insulation properties, their thermal conductivity is low and cannot meet the growing heat dissipation needs of modern electronic devices. Such materials include some traditional polymer insulators and certain types of ceramic materials, which perform well in ensuring electrical safety, but may cause equipment overheating under high heat loads, affecting performance and reliability.

[0004] Therefore, how to resolve the contradiction between thermal management and electrical safety of existing materials is an urgent problem that technicians in this field need to solve. Summary of the invention

[0005] In view of this, the purpose of the present invention is to provide an insulating high thermal conductivity gel and a preparation method thereof in view of the defects that most existing thermal conductive gels have a thermal conductivity coefficient of less than 5W / (m·K), and mainly achieve high thermal conductivity by adding conductive fillers. They are conductive themselves and therefore cannot meet the heat dissipation requirements of increasingly sophisticated electronic devices.

[0006] Specifically, modified copper powder, modified boron nitride and nano metal droplets are prepared respectively, solid modified fillers with high thermal conductivity and liquid metal are used to form solid-liquid mixed fillers, and then added to the organic silicon gel to prepare the thermally conductive gel. The present invention utilizes the synergistic effect of the three fillers to achieve high thermal conductivity and insulation of the thermally conductive gel. The thermal conductivity of the prepared gel material is greater than 6.5W / (m·K) and the volume resistivity is greater than 10 9 Ω·cm.

[0007] In order to achieve the above object, the present invention adopts the following technical solution:

[0008] The first technical purpose of the present invention is to provide an insulating high thermal conductivity gel, comprising the following raw materials in parts by weight:

[0009]

[0010] Optionally, the modified copper powder is obtained by modifying copper powder with a silane coupling agent, and the silane coupling agent is one or more combinations of aminopropyl triethoxysiloxane, γ-aminopropyl aminoethyl trimethylsiloxane, aminopropyl trimethoxysiloxane or glycidyloxypropyl trimethylsiloxane;

[0011] The modified boron nitride is a boron nitride nanosheet obtained by dispersing and exfoliating hexagonal boron nitride, and then the boron nitride nanosheet is modified by a silane coupling agent, and the silane coupling agent is one or more combinations of aminopropyl triethoxysiloxane, γ-aminopropyl aminoethyl trimethylsiloxane, aminopropyl trimethoxysiloxane or glycidyl ether oxypropyl trimethylsiloxane;

[0012] The nano metal droplets are obtained by ultrasonic treatment of liquid metal, and the liquid metal is one of gallium-indium alloy, gallium-indium-tin alloy, and gallium-tin alloy.

[0013] Optionally, the inhibitor is one or more combinations of 1-ethynyl-1-cyclohexanol, 2-methyl-3-butynyl-2-ol, 3,5-dimethyl-1-hexynyl-3-ol, and 3-methyl-1-dodecyn-3-ol.

[0014] Optionally, the catalyst is one or more combinations of chloroplatinic acid, Karstedt catalyst, Ashby catalyst, Speier catalyst, Lamoreaux catalyst and Castel catalyst.

[0015] The second technical purpose of the present invention is to provide a method for preparing the insulating high thermal conductive gel as described above, which specifically comprises the following steps:

[0016] S1, mixing double-terminal vinyl silicone oil, side-chain hydrogen-containing silicone oil, terminal hydrogen-containing silicone oil and inhibitor under 20-300W ultrasound for 5-120 minutes, and then vacuum degassing to form a silicone rubber matrix;

[0017] S2, mixing the modified copper powder, modified boron nitride and nano-metal droplets, and then mixing them with the silicone rubber matrix, adding a catalyst, mixing in a planetary mixer for 5 to 60 minutes, and performing vacuum degassing;

[0018] S3. Roll the deaerated mixture through a three-roller machine into a sheet sample with a thickness of 0.5 to 50 mm, put it into a drying oven, and cure it at 80 to 120° C. for 1 to 4 hours to obtain the insulating and highly thermally conductive gel.

[0019] It should be noted that the copper powder is micron-sized and relatively large in size. It can be better dispersed in silicone resin through silanization modification. The combination of micron-sized copper powder and nano-sized liquid metal helps to form a three-dimensional thermal conductive network and improve the thermal conductivity. Boron nitride is a two-dimensional material with high thermal conductivity and non-electrical conductivity. Its two-dimensional structure is easy to aggregate. Silanization modification can prevent its aggregation and make it better dispersed in silicone resin. In addition, after modification, it can be dispersed between copper powder and liquid metal, blocking the electrons of copper powder and liquid metal to form a long-range conductive network, thereby keeping the system insulated.

[0020] Furthermore, the preparation method of the modified copper powder comprises the following steps:

[0021] Cu1. Disperse 0.6-4μm copper powder in ethanol, and then ultrasonically clean it for 10-60min under 10-100W ultrasound, where the amount of ethanol is 3-10 times the mass of the copper powder;

[0022] Cu2, centrifugally separating the copper powder and ethanol, adding the washed copper powder to a toluene solution containing a silane coupling agent, stirring at 40-80° C. at a speed of 300-1000 rpm for 12-24 hours, wherein the mass of the silane coupling agent is 2%-8% of the copper powder, the mass of toluene is 50-200 times that of the silane coupling agent, and the silane coupling agent is one or more combinations of aminopropyl triethoxysiloxane, γ-aminopropyl aminoethyl trimethylsiloxane, aminopropyl trimethoxysiloxane or glycidyl ether oxypropyl trimethylsiloxane;

[0023] Cu3, centrifugally remove the solvent and unreacted silane coupling agent, wash with ethanol 3 to 5 times, and then dry in an oven at 60 to 80° C. for 12 to 24 hours to obtain the modified copper powder.

[0024] Furthermore, the preparation method of the modified boron nitride comprises the following steps:

[0025] BN1, dispersing hexagonal boron nitride powder in a mixed solution of isopropanol and deionized water, and ultrasonically exfoliating for 12 to 24 hours under 100 to 500W ultrasound, wherein the volume ratio of isopropanol to deionized water is 1:1, and the mass ratio of hexagonal boron nitride powder to deionized water is 0.05 to 0.2;

[0026] BN2, the dispersion obtained above is centrifuged at 1000-3000 rpm for 5-30 min to remove the unpeeled hexagonal boron nitride, the supernatant is further centrifuged at 10000-20000 rpm for 30-60 min, and the obtained solid is dried at 80-100° C. for 8-12 h to obtain boron nitride nanosheets;

[0027] BN3, adding the above-mentioned boron nitride nanosheets to a toluene solution containing a silane coupling agent, stirring and reacting at a speed of 300-1000 rpm at 40-80°C for 12-24 hours, wherein the mass of the silane coupling agent is 1%-3% of the boron nitride nanosheets, the mass of toluene is 50-200 times that of the boron nitride nanosheets, and the silane coupling agent is one or more combinations of aminopropyl triethoxysiloxane, γ-aminopropyl aminoethyl trimethylsiloxane, aminopropyl trimethoxysiloxane or glycidyl ether oxypropyl trimethylsiloxane;

[0028] BN4, centrifuge to remove the solvent and unreacted silane coupling agent, wash with ethanol 3 to 5 times, and then dry in an oven at 60 to 100° C. for 8 to 24 hours to obtain the modified boron nitride.

[0029] Furthermore, the method for preparing the nano-metal droplets specifically comprises the following steps:

[0030] Ultrasonic treatment is performed at 200-500W for 0.2-2h to form nano-metal droplets from the liquid metal, wherein the liquid metal is one of gallium-indium alloy, gallium-indium-tin alloy and gallium-tin alloy.

[0031] It should be noted that, in the present invention, on the one hand, the use of modified copper powder, modified boron nitride and nano-metal droplets can improve the interfacial compatibility between the filler and the polymer matrix, reduce the interfacial thermal resistance, and thus enhance the thermal conductivity of the composite material; on the other hand, the modified copper powder and nano-metal droplets construct an efficient heat conduction network, and the boron nitride not only provides a uniform heat conduction path, but also the layered boron nitride can effectively block electron migration, so that the electrical insulation of the gel material can be maintained.

[0032] Moreover, the thermal conductivity of the insulating high thermal conductivity gel prepared by the present invention is greater than 6.5W / (m·K) and the resistivity is greater than 10 9 Ω·cm.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] (1) The present invention aims at the fact that the thermal conductivity coefficient of existing thermal conductive gel is not high enough, and high thermal conductivity is achieved mainly by adding conductive fillers, which are themselves conductive. The present invention proposes to use modified copper powder and nano-metal droplets to construct an efficient heat conduction network, and boron nitride further provides a heat conduction path, while blocking electron migration, to prepare an insulating high thermal conductivity gel. At the same time, a preparation method of modified copper powder, modified boron nitride and nano-metal droplets is proposed to improve the interface compatibility between the filler and the gel matrix, reduce the interface thermal resistance, and thus enhance the thermal conductivity of the composite material.

[0035] (2) The thermal conductivity of the insulating high thermal conductivity gel prepared by the method of the present invention is greater than 6.5W / (m·K) and the resistivity is greater than 10 9 Ω·cm.

[0036] (3) The preparation method of the insulating high thermal conductive gel of the present invention is simple, has low equipment requirements, and the prepared gel material has excellent performance, and is suitable for industrial continuous and mass production. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0038] Figure 1 This is a graph of the volume resistivity of the insulating and highly thermally conductive gel prepared in Example 2. DETAILED DESCRIPTION

[0039] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0040] The word "embodiment" used here as an "exemplary" does not necessarily mean that any embodiment described is superior to or better than other embodiments. Unless otherwise specified, the performance index tests in the embodiments of this application are performed using conventional test methods in the art. It should be understood that the terms described in this application are only used to describe specific implementation methods and are not used to limit the content disclosed in this application.

[0041] Unless otherwise specified, the technical and scientific terms used in this document have the same meanings as commonly understood by ordinary technicians in the technical field to which this application belongs; other experimental methods and technical means not specifically specified in this application refer to experimental methods and technical means commonly used by ordinary technicians in this field.

[0042] In order to better illustrate the content of the present application, numerous specific details are provided in the specific examples below. It should be understood by those skilled in the art that the present application can also be implemented without certain specific details. In the embodiments, some methods, means, instruments, equipment, etc. well known to those skilled in the art are not described in detail in order to highlight the main purpose of the present application.

[0043] Under the premise of no conflict, the technical features disclosed in the embodiments of the present application can be combined arbitrarily, and the resulting technical solutions belong to the contents disclosed in the embodiments of the present application.

[0044] The invention discloses an insulating high-thermal conductive gel and a preparation method thereof.

[0045] In order to better understand the present invention, the present invention is further specifically described below through the following examples, but it should not be understood as a limitation of the present invention. Some non-essential improvements and adjustments made by technicians in this field based on the above invention content are also considered to fall within the protection scope of the present invention.

[0046] Example 1

[0047] Preparation of modified copper powder:

[0048] Cu1, 20g 1 μm copper particles were dispersed in 100 g ethanol and then ultrasonically cleaned at 50 W for 20 min;

[0049] Cu2, centrifugation to separate the copper powder and ethanol, add 10g of the washed copper powder to 50g of toluene solution containing 0.5g of aminopropyl triethoxysiloxane, and stir at 60°C at a speed of 600rpm for 20h;

[0050] Cu3, centrifugation to remove the solvent and unreacted silane coupling agent, and washed with ethanol three times, and then dried in an oven at 60°C for 24h to obtain modified copper powder.

[0051] Preparation of modified boron nitride:

[0052] BN1, 5g of hexagonal boron nitride powder was dispersed in a mixed solution of 50g of isopropanol and 50g of deionized water, and ultrasonically stripped at 300W for 24h;

[0053] BN2, the dispersion obtained above was centrifuged at 2000 rpm for 10 min to remove the unpeeled hexagonal boron nitride, the supernatant was further centrifuged at 10000 rpm for 30 min, and the obtained solid was dried at 80 ° C for 12 h to obtain boron nitride nanosheets;

[0054] BN3, add 1g of the above boron nitride nanosheets to 100g of toluene solution containing 0.02g of aminopropyl triethoxysiloxane, and stir at 500rpm at 60°C for 12h;

[0055] BN4, centrifuge to remove the solvent and unreacted silane coupling agent, wash with ethanol three times, and then dry in an oven at 80°C for 24 hours to obtain modified boron nitride.

[0056] Preparation of nanometal droplets:

[0057] The liquid metal gallium-indium alloy was ultrasonically treated for 40 minutes at 300W to form nano-metal droplets.

[0058] Preparation of thermal conductive gel:

[0059] S1, 40 parts of double-terminal vinyl silicone oil, 40 parts of side-chain hydrogen-containing silicone oil, 20 parts of terminal hydrogen-containing silicone oil and 0.5 parts of 1-ethynyl-1-cyclohexanol were mixed under 50W ultrasound for 20 minutes, followed by vacuum degassing to form a silicone rubber matrix;

[0060] S2, 50 parts of modified copper powder, 25 parts of modified boron nitride and 50 parts of nano metal droplets are mixed, and then mixed with a silicone rubber matrix, 1.0 part of chloroplatinic acid is added, and mixed in a planetary mixer for 30 minutes, and vacuum degassing is performed;

[0061] S3. The deaerated mixture is rolled into a sheet sample with a thickness of 1 mm by a three-roller machine, placed in a drying oven, and cured at 80° C. for 4 h to obtain a sample thermal conductive gel.

[0062] The thermal conductivity of the insulating high thermal conductive gel is 7.02W / (m·K), and the volume resistivity at 10Hz is 1.2×10 9 Ω·cm.

[0063] Example 2

[0064] Preparation of modified copper powder: consistent with Example 1.

[0065] Preparation of modified boron nitride: consistent with Example 1.

[0066] Preparation of nano-metal droplets: the same as in Example 1.

[0067] Preparation of thermal conductive gel:

[0068] S1, 40 parts of double-terminal vinyl silicone oil, 40 parts of side-chain hydrogen-containing silicone oil, 20 parts of terminal hydrogen-containing silicone oil and 0.5 parts of 1-ethynyl-1-cyclohexanol were mixed under 50W ultrasound for 20 minutes, followed by vacuum degassing to form a silicone rubber matrix;

[0069] S2, 25 parts of modified copper powder, 25 parts of modified boron nitride and 25 parts of nano metal droplets are mixed, and then mixed with a silicone rubber matrix, 1.0 part of chloroplatinic acid is added, and mixed in a planetary mixer for 30 minutes, and vacuum degassing is performed;

[0070] S3. The deaerated mixture is rolled into a sheet sample with a thickness of 1 mm by a three-roller machine, placed in a drying oven, and cured at 80° C. for 4 h to obtain a sample thermal conductive gel.

[0071] The thermal conductivity of the insulating high thermal conductive gel is 6.51 W / (m·K), and the volume resistivity at 10 Hz is 3.0×10 9 Ω·cm.

[0072] Example 3

[0073] Preparation of modified copper powder: consistent with Example 1.

[0074] Preparation of modified boron nitride: consistent with Example 1.

[0075] Preparation of nano-metal droplets: the same as in Example 1.

[0076] Preparation of thermal conductive gel:

[0077] S1, 40 parts of double-terminal vinyl silicone oil, 40 parts of side-chain hydrogen-containing silicone oil, 20 parts of terminal hydrogen-containing silicone oil and 0.5 parts of 1-ethynyl-1-cyclohexanol were mixed under 50W ultrasound for 20 minutes, followed by vacuum degassing to form a silicone rubber matrix;

[0078] S2, 20 parts of modified copper powder, 20 parts of modified boron nitride and 30 parts of nano metal droplets are mixed, and then mixed with a silicone rubber matrix, 1.0 part of chloroplatinic acid is added, and mixed in a planetary mixer for 30 minutes, and vacuum degassing is performed;

[0079] S3. The deaerated mixture is rolled into a sheet sample with a thickness of 1 mm by a three-roller machine, placed in a drying oven, and cured at 80° C. for 4 h to obtain a sample thermal conductive gel.

[0080] The thermal conductivity of the insulating high thermal conductive gel is 6.62W / (m·K), and the volume resistivity at 10Hz is 2.1×10 9 Ω·cm.

[0081] Example 4

[0082] Preparation of modified copper powder: consistent with Example 1.

[0083] Preparation of modified boron nitride: consistent with Example 1.

[0084] Preparation of nano-metal droplets: the same as in Example 1.

[0085] Preparation of thermal conductive gel:

[0086] S1, 40 parts of double-terminal vinyl silicone oil, 40 parts of side-chain hydrogen-containing silicone oil, 20 parts of terminal hydrogen-containing silicone oil and 0.5 parts of 1-ethynyl-1-cyclohexanol were mixed under 50W ultrasound for 20 minutes, followed by vacuum degassing to form a silicone rubber matrix;

[0087] S2, 20 parts of modified copper powder, 20 parts of modified boron nitride and 20 parts of nano metal droplets are mixed, and then mixed with a silicone rubber matrix, 1.0 part of chloroplatinic acid is added, and mixed in a planetary mixer for 30 minutes, and vacuum degassing is performed;

[0088] S3. The deaerated mixture is rolled into a sheet sample with a thickness of 1 mm by a three-roller machine, placed in a drying oven, and cured at 80° C. for 4 h to obtain a sample thermal conductive gel.

[0089] The thermal conductivity of the insulating high thermal conductive gel is 6.59W / (m·K), and the volume resistivity at 10Hz is 2.0×10 9 Ω·cm.

[0090] Example 5

[0091] Preparation of modified copper powder: consistent with Example 1.

[0092] Preparation of modified boron nitride: consistent with Example 1.

[0093] Preparation of nano-metal droplets: the same as in Example 1.

[0094] Preparation of thermal conductive gel:

[0095] S1, 60 parts of double-terminal vinyl silicone oil, 30 parts of side chain hydrogen silicone oil, 10 parts of terminal hydrogen silicone oil and 0.5 parts of 1-ethynyl-1-cyclohexanol were mixed under 50W ultrasound for 20 minutes, and then vacuum degassed to form a silicone rubber matrix;

[0096] S2, 25 parts of modified copper powder, 25 parts of modified boron nitride and 25 parts of nano metal droplets are mixed, and then mixed with a silicone rubber matrix, 1.0 part of chloroplatinic acid-isopropanol complex is added, and mixed in a planetary mixer for 30 minutes, and vacuum degassing is performed;

[0097] S3. The deaerated mixture is rolled into a sheet sample with a thickness of 1 mm by a three-roller machine, placed in a drying oven, and cured at 80° C. for 4 h to obtain a sample thermal conductive gel.

[0098] The thermal conductivity of the insulating high thermal conductive gel is 6.65W / (m·K), and the volume resistivity at 10Hz is 3.2×10 9 Ω·cm.

[0099] Example 6

[0100] Preparation of modified copper powder:

[0101] Cu1, 20g 1 μm copper particles were dispersed in 100 g ethanol and then ultrasonically cleaned at 50 W for 20 min;

[0102] Cu2, centrifugation to separate the copper powder and ethanol, add 10g of the washed copper powder to 50g of toluene solution containing 0.5g of γ-aminopropylaminoethyltrimethylsiloxane, and stir at 60°C at a speed of 600rpm for 20h;

[0103] Cu3, centrifugation to remove the solvent and unreacted silane coupling agent, and washed with ethanol three times, and then dried in an oven at 60°C for 24h to obtain modified copper powder.

[0104] Preparation of modified boron nitride: consistent with Example 1.

[0105] Preparation of nano-metal droplets: the same as in Example 1.

[0106] Preparation of thermal conductive gel:

[0107] S1, 60 parts of double-terminal vinyl silicone oil, 20 parts of side chain hydrogen silicone oil, 10 parts of terminal hydrogen silicone oil and 0.5 parts of 1-ethynyl-1-cyclohexanol were mixed under 50W ultrasound for 20 minutes, and then vacuum degassed to form a silicone rubber matrix;

[0108] S2, 20 parts of modified copper powder, 25 parts of modified boron nitride and 30 parts of nano metal droplets are mixed, and then mixed with a silicone rubber matrix, 1.0 part of chloroplatinic acid is added, and mixed in a planetary mixer for 30 minutes, and vacuum degassing is performed;

[0109] S3. The deaerated mixture is rolled into a sheet sample with a thickness of 1 mm by a three-roller machine, placed in a drying oven, and cured at 80° C. for 4 h to obtain a sample thermal conductive gel.

[0110] The thermal conductivity of the insulating high thermal conductive gel is 6.85W / (m·K), and the volume resistivity at 10Hz is 1.5×10 9 Ω·cm.

[0111] Example 7

[0112] Preparation of modified copper powder: consistent with Example 1.

[0113] Preparation of modified boron nitride:

[0114] BN1, 5g of hexagonal boron nitride powder was dispersed in a mixed solution of 50g of isopropanol and 50g of deionized water, and ultrasonically stripped at 300W for 24h;

[0115] BN2, the dispersion obtained above was centrifuged at 2000 rpm for 10 min to remove the unpeeled hexagonal boron nitride, the supernatant was further centrifuged at 10000 rpm for 30 min, and the obtained solid was dried at 80 ° C for 12 h to obtain boron nitride nanosheets;

[0116] BN3, add 1g of the above boron nitride nanosheets to 100g of toluene solution containing 0.03g of aminopropyltrimethoxysiloxane, and stir at 500rpm at 60°C for 12h;

[0117] BN4, centrifuge to remove the solvent and unreacted silane coupling agent, wash with ethanol three times, and then dry in an oven at 80°C for 24 hours to obtain modified boron nitride.

[0118] Preparation of nano-metal droplets: the same as in Example 1.

[0119] Preparation of thermal conductive gel:

[0120] S1, 40 parts of double-terminal vinyl silicone oil, 40 parts of side-chain hydrogen-containing silicone oil, 20 parts of terminal hydrogen-containing silicone oil and 0.5 parts of 1-ethynyl-1-cyclohexanol were mixed under 50W ultrasound for 20 minutes, followed by vacuum degassing to form a silicone rubber matrix;

[0121] S2, 30 parts of modified copper powder, 20 parts of modified boron nitride and 20 parts of nano metal droplets are mixed, and then mixed with a silicone rubber matrix, 1.0 part of chloroplatinic acid is added, and mixed in a planetary mixer for 30 minutes, and vacuum degassing is performed;

[0122] S3. The degassed mixture is rolled into a sheet sample with a thickness of 1 mm by a three-roller machine, placed in a drying oven, and cured at 120° C. for 2 h to obtain a sample thermal conductive gel.

[0123] The thermal conductivity of the insulating high thermal conductive gel is 6.95 W / (m·K), and the volume resistivity at 10 Hz is 1.1×10 9 Ω·cm.

[0124] Example 8

[0125] Preparation of modified copper powder: consistent with Example 1.

[0126] Preparation of modified boron nitride: consistent with Example 1.

[0127] Preparation of nanometal droplets:

[0128] Ultrasonication was performed at 400W for 30 minutes to form nano-metal droplets from the liquid metal gallium indium tin alloy.

[0129] Preparation of thermal conductive gel:

[0130] S1, 50 parts of double-terminal vinyl silicone oil, 20 parts of side chain hydrogen silicone oil, 10 parts of terminal hydrogen silicone oil and 0.5 parts of 1-ethynyl-1-cyclohexanol were mixed under 50W ultrasound for 20 minutes, and then vacuum degassed to form a silicone rubber matrix;

[0131] S2, 25 parts of modified copper powder, 20 parts of modified boron nitride and 25 parts of nano metal droplets are mixed, and then mixed with a silicone rubber matrix, 1.0 part of chloroplatinic acid is added, and mixed in a planetary mixer for 30 minutes, and vacuum degassing is performed;

[0132] S3. The degassed mixture is rolled into a sheet sample with a thickness of 1 mm by a three-roller machine, placed in a drying oven, and cured at 120° C. for 2 h to obtain a sample thermal conductive gel.

[0133] The thermal conductivity of the insulating high thermal conductive gel is 6.75W / (m·K), and the volume resistivity at 10Hz is 2.5×10 9 Ω·cm.

[0134] In order to further demonstrate the beneficial effects of the present invention and to better understand the present invention, the following comparative examples are used to further illustrate the technical features disclosed in the present invention, but they should not be construed as limiting the present invention. Other improvements made by those skilled in the art based on the above invention content without inventive work are also considered to fall within the scope of protection of the present invention.

[0135] Comparative Example 1

[0136] Preparation of modified copper powder: consistent with Example 1.

[0137] Preparation of nano-metal droplets: the same as in Example 1.

[0138] Preparation of thermal conductive gel:

[0139] S1, 40 parts of double-terminal vinyl silicone oil, 40 parts of side-chain hydrogen-containing silicone oil, 20 parts of terminal hydrogen-containing silicone oil and 0.5 parts of 1-ethynyl-1-cyclohexanol were mixed under 50W ultrasound for 20 minutes, followed by vacuum degassing to form a silicone rubber matrix;

[0140] S2, 25 parts of modified copper powder and 25 parts of nano metal droplets are mixed, and then mixed with a silicone rubber matrix, 1.0 part of chloroplatinic acid is added, and mixed in a planetary mixer for 30 minutes, and vacuum degassing is performed;

[0141] S3. The deaerated mixture is rolled into a sheet sample with a thickness of 1 mm by a three-roller machine, placed in a drying oven, and cured at 80° C. for 4 h to obtain a sample thermal conductive gel.

[0142] The thermal conductivity of the insulating high thermal conductive gel is 5.57W / (m·K), and the volume resistivity at 10Hz is 2.3×10 4 Ω·cm.

[0143] Comparative Example 2

[0144] Preparation of modified copper powder: consistent with Example 1.

[0145] Preparation of modified boron nitride: consistent with Example 1.

[0146] Preparation of thermal conductive gel:

[0147] S1, 40 parts of double-terminal vinyl silicone oil, 40 parts of side-chain hydrogen-containing silicone oil, 20 parts of terminal hydrogen-containing silicone oil and 0.5 parts of 1-ethynyl-1-cyclohexanol were mixed under 50W ultrasound for 20 minutes, followed by vacuum degassing to form a silicone rubber matrix;

[0148] S2, 20 parts of modified boron nitride and 30 parts of nano-metal droplets are mixed, and then mixed with a silicone rubber matrix, 1.0 part of chloroplatinic acid is added, and mixed in a planetary mixer for 30 minutes, and vacuum degassing is performed;

[0149] S3. The deaerated mixture is rolled into a sheet sample with a thickness of 1 mm by a three-roller machine, placed in a drying oven, and cured at 80° C. for 4 h to obtain a sample thermal conductive gel.

[0150] The thermal conductivity of the insulating high thermal conductive gel is 4.21 W / (m·K), and the volume resistivity at 10 Hz is 2.2×10 9 Ω·cm.

[0151] Comparative Example 3

[0152] Preparation of modified boron nitride: consistent with Example 1.

[0153] Preparation of nano-metal droplets: the same as in Example 1.

[0154] Preparation of thermal conductive gel:

[0155] S1, 40 parts of double-terminal vinyl silicone oil, 40 parts of side-chain hydrogen-containing silicone oil, 20 parts of terminal hydrogen-containing silicone oil and 0.5 parts of 1-ethynyl-1-cyclohexanol were mixed under 50W ultrasound for 20 minutes, followed by vacuum degassing to form a silicone rubber matrix;

[0156] S2, 25 parts of modified copper powder and 25 parts of modified boron nitride are mixed, and then mixed with a silicone rubber matrix, 1.0 part of chloroplatinic acid is added, and mixed in a planetary mixer for 30 minutes, and vacuum degassing is performed;

[0157] S3. The deaerated mixture is rolled into a sheet sample with a thickness of 1 mm by a three-roller machine, placed in a drying oven, and cured at 80° C. for 4 h to obtain a sample thermal conductive gel.

[0158] The thermal conductivity of the insulating high thermal conductive gel is 3.77W / (m·K), and the volume resistivity at 10Hz is 1.2×10 10 Ω·cm.

[0159] In addition, in order to further illustrate / verify the superiority of the technology of the present invention, the inventors also conducted the following performance tests:

[0160] The insulating high thermal conductive gels prepared in Examples 1-8 and the thermal conductive gels prepared in Comparative Examples 1-3 were respectively tested for their thermal conductivity values ​​and volume resistivity values. The results are shown in Table 1.

[0161] Table 1 Thermal conductivity and volume resistivity of thermally conductive gels of Examples 1-8 and Comparative Examples 1-3

[0162] Thermally conductive gel Thermal conductivity W / (m·K) Volume resistivity Ω·cm at 10Hz Example 1 7.02 <![CDATA[1.2×10 9 ]]> Example 2 6.51 <![CDATA[3.0×10 9 ]]> Example 3 6.62 <![CDATA[2.1×10 9 ]]> Example 4 6.59 <![CDATA[2.0×10 9 ]]> Example 5 6.65 <![CDATA[3.2×10 9 ]]> Example 6 6.85 <![CDATA[1.5×10 9 ]]> Example 7 6.95 <![CDATA[1.1×10 9 ]]> Example 8 6.75 <![CDATA[2.5×10 9 ]]> Comparative Example 1 5.57 <![CDATA[2.3×10 4 ]]> Comparative Example 2 4.21 <![CDATA[2.2×10 9 ]]> Comparative Example 3 3.77 <![CDATA[1.2×10 10 ]]>

[0163] As can be seen from Table 1, the thermally conductive gels prepared in Examples 1-8 have high thermal conductivity and volume resistivity; in Comparative Example 1, due to the lack of boron nitride, its thermal conductivity is slightly reduced, and its electrical conductivity is significantly increased, indicating that modified boron nitride plays an important role in improving insulation; Comparative Examples 2 and 3 are respectively without adding modified copper powder and nano-metal droplets, and the thermal conductivity of the prepared thermally conductive gels is reduced, indicating that both of them can improve the thermal conductivity of the system.

[0164] The above experiments show that the present invention utilizes the synergistic effect of the three fillers to achieve high thermal conductivity and insulation of the thermally conductive gel. The thermal conductivity of the prepared gel material is greater than 6.5 W / (m·K) and the volume resistivity is greater than 10 9 Ω·cm; and the preparation method of the insulating high thermal conductive gel of the present invention is simple, the equipment requirements are low, the prepared gel material has excellent performance, and is suitable for industrial continuous and mass production.

[0165] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. An insulating high thermal conductivity gel, characterized in that: The insulating high thermal conductive gel comprises the following raw materials in parts by weight: 20-100 parts of double-terminated vinyl silicone oil; 20-40 parts of side chain hydrogen silicone oil; The end contains 20 to 40 parts of hydrogen silicone oil; 20-40 parts of modified copper powder; 10-30 parts of modified boron nitride; 20 to 40 parts of nano metal droplets; 0.1 to 5 parts of inhibitor; 0.2 to 5 parts of catalyst.

2. The insulating high thermal conductivity gel according to claim 1, characterized in that: The modified copper powder is obtained by modifying the copper powder with a silane coupling agent, wherein the silane coupling agent is one or more of aminopropyl triethoxysiloxane, γ-aminopropyl aminoethyl trimethylsiloxane, aminopropyl trimethoxysiloxane or glycidyloxypropyl trimethylsiloxane; The modified boron nitride is a boron nitride nanosheet obtained by dispersing and exfoliating hexagonal boron nitride, and then the boron nitride nanosheet is modified by a silane coupling agent, and the silane coupling agent is one or more combinations of aminopropyl triethoxysiloxane, γ-aminopropyl aminoethyl trimethylsiloxane, aminopropyl trimethoxysiloxane or glycidyl ether oxypropyl trimethylsiloxane; The nano metal droplets are obtained by ultrasonic treatment of liquid metal, and the liquid metal is one of gallium-indium alloy, gallium-indium-tin alloy, and gallium-tin alloy.

3. The insulating high thermal conductivity gel according to claim 1, characterized in that: The inhibitor is one or more of 1-ethynyl-1-cyclohexanol, 2-methyl-3-butynyl-2-ol, 3,5-dimethyl-1-hexynyl-3-ol, and 3-methyl-1-dodecyn-3-ol.

4. The insulating high thermal conductivity gel according to claim 1, characterized in that: The catalyst is one or more combinations of chloroplatinic acid, Karstedt catalyst, Ashby catalyst, Speier catalyst, Lamoreaux catalyst and Custer catalyst.

5. A method for preparing the insulating high thermal conductive gel according to claim 1, characterized in that: The preparation method of the insulating high thermal conductive gel comprises the following steps: S1, mixing double-terminal vinyl silicone oil, side-chain hydrogen-containing silicone oil, terminal hydrogen-containing silicone oil and inhibitor under 20-300W ultrasound for 5-120 minutes, and then vacuum degassing to form a silicone rubber matrix; S2, mixing the modified copper powder, modified boron nitride and nano-metal droplets, and then mixing them with the silicone rubber matrix prepared in S1, adding a catalyst, mixing in a planetary mixer for 5 to 60 minutes, and performing vacuum degassing; S3. The degassed mixture of S2 is rolled into a sheet sample with a thickness of 0.5 to 50 mm by a three-roller machine, and then placed in a drying oven and cured at 80 to 120° C. for 1 to 4 hours to obtain the insulating and highly thermally conductive gel.

6. The method for preparing the insulating high thermal conductive gel according to claim 4, characterized in that: The preparation steps of the modified copper powder are as follows: Cu1. Disperse 0.6-4μm copper powder in ethanol, and then ultrasonically clean it for 10-60min under 10-100W ultrasound, where the amount of ethanol is 3-10 times the mass of the copper powder; Cu2, centrifugally separating the copper powder and ethanol, adding the washed copper powder to a toluene solution containing a silane coupling agent, stirring at 40-80° C. at a speed of 300-1000 rpm for 12-24 hours, wherein the mass of the silane coupling agent is 2%-8% of the copper powder, the mass of toluene is 50-200 times that of the silane coupling agent, and the silane coupling agent is one or more combinations of aminopropyl triethoxysiloxane, γ-aminopropyl aminoethyl trimethylsiloxane, aminopropyl trimethoxysiloxane or glycidyl ether oxypropyl trimethylsiloxane; Cu3, centrifugally remove the solvent and unreacted silane coupling agent, wash with ethanol 3 to 5 times, and then dry in an oven at 60 to 80° C. for 12 to 24 hours to obtain the modified copper powder.

7. The method for preparing the insulating high thermal conductive gel according to claim 4, characterized in that: The preparation steps of the modified boron nitride are as follows: BN1, dispersing hexagonal boron nitride powder in a mixed solution of isopropanol and deionized water, and ultrasonically exfoliating for 12 to 24 hours under 100 to 500W ultrasound, wherein the volume ratio of isopropanol to deionized water is 1:1, and the mass ratio of hexagonal boron nitride powder to deionized water is 0.05 to 0.2; BN2, the dispersion obtained above is centrifuged at 1000-3000 rpm for 5-30 min to remove the unpeeled hexagonal boron nitride, the supernatant is further centrifuged at 10000-20000 rpm for 30-60 min, and the obtained solid is dried at 80-100° C. for 8-12 h to obtain boron nitride nanosheets; BN3, adding the above-mentioned boron nitride nanosheets to a toluene solution containing a silane coupling agent, stirring and reacting at a speed of 300-1000 rpm at 40-80°C for 12-24 hours, wherein the mass of the silane coupling agent is 1%-3% of the boron nitride nanosheets, the mass of toluene is 50-200 times that of the boron nitride nanosheets, and the silane coupling agent is one or more combinations of aminopropyl triethoxysiloxane, γ-aminopropyl aminoethyl trimethylsiloxane, aminopropyl trimethoxysiloxane or glycidyl ether oxypropyl trimethylsiloxane; BN4, centrifuge to remove the solvent and unreacted silane coupling agent, wash with ethanol 3 to 5 times, and then dry in an oven at 60 to 100° C. for 8 to 24 hours to obtain the modified boron nitride.

8. The method for preparing the insulating high thermal conductive gel according to claim 4, characterized in that: The steps for preparing the nano metal droplets are as follows: Ultrasonic treatment is performed at 200-500W for 0.2-2h to form nano-metal droplets from the liquid metal, wherein the liquid metal is one of gallium-indium alloy, gallium-indium-tin alloy and gallium-tin alloy.

Citation Information

Cited By

  • Heat-conducting gel based on Cu-based core-shell structure heat-conducting filler and preparation method of heat-conducting gel

    CN121045828A

  • Preparation method of high-thermal-conductivity insulating silica gel encapsulating material for electromechanical component equipment

    CN122080850A